Molecular understanding of unusual HbE-β+-thalassemia with Hb phenotype similar to HbE heterozygote: simple and rapid differentiation using HbE levels - Wittaya Jomoui; Surada Satthakarn; Sitthichai Panyasai (Annals of Medicine, 2023)
AbstractBackground Low HbF expression in HbE-β+-thalassemia may lead to misdiagnosis of HbE heterozygosity. We aimed to characterize the β- and α-globin genes and the modifying factors related to HbF expression in patients with an Hb phenotype similar to that of HbE heterozygotes. Furthermore, screening tools for differentiating HbE-β+-thalassemia from HbE heterozygotes have been investigated.Participants and Methods A total of 2133 participants with HbE and HbA with varying HbF levels were recruited. Polymerase chain reaction-based DNA analysis and sequencing were performed to characterize β- and α-globin genes. DNA polymorphism at position −158 nt 5′ to Gγ-globin was performed by XmnI restriction digestion. Receiver operating characteristic (ROC) curves were constructed using the area under the curve (AUC). Cutoff values of HbA2, HbE, and HbF levels for the differentiation of HbE-β+-thalassemia from HbE heterozygotes were determined.Results Five β+-thalassemia mutations trans to βE-gene (β−87(C>A), β−31(A>G), β−28(A>G), β19(A>G), and β126(T>G)) were identified in 79 patients. Among these, 54 presented with low HbF levels, and 25 presented with high HbF levels. ROC curve analysis revealed an excellent AUC of 1.000 (95% confidence interval:1.000–1.000) for HbE levels, and a cut-off point of ≥35.0% had 100.0% sensitivity, specificity, and Youden’s index for differentiating HbE-β+-thalassemia from HbE heterozygotes. The proportion of α-thalassemia mutations was 46.3 and 8.0% among HbE-β+-thalassemia patients with low and high HbF levels, respectively. Two rare α-thalassemia mutations (Cap +14(C>G) and initiation codon (ATG>-TG)) of α2-globin genes were identified. The genotype and allele of the polymorphism at −158 nt 5′ to Gγ-globin was found to be negatively associated with HbF expression.Conclusions HbE-β+-thalassemia cannot be disregarded until appropriate DNA analysis is performed, and the detection of α-thalassemia mutations should always be performed under these conditions. An HbE level ≥35.0% may indicate screening of samples for DNA analysis for HbE-β+-thalassemia diagnosis.